# Exercise 6.1

On the following page we have given the solution of Exercise 6.1 of Mathematics 9 (Science) published by Caravan Book House, Lahore.

We have created this page and it will be updated to add new solutions occasionally. Please stay in touch with this page.

Find the H.C.F of the following expressions.
(i) $39x^7y^3z$ and $91x^5y^6 z^7$
(ii) $102xy^2z$, $85x^2yz$ and $187xyz^2$

Solution:

(i) $39x^7y^3z=13\times 3\times x^7 y^3 z$
$91x^5y^6 z^7=13\times 7\times x^5 y^6 z^7$
H.C.F = $13 x^5y^3z$

(ii) $102xy^2z=2\times 3\times 17 xy^2z$
$85x^2yz=3\times 17 x^2 y z$
$187xyz^2 = 11\times 17 xyz^2$
H.C.F= $17 xyz$

Find the H.C.F of the following expressions by factorization.
(i) $x^2+5x+6$, $x^2-4x-12$
(ii) $x^3-27$, $x^2+6x-27$, $2x^2-18$
(iii) $x^3-2x^2+x$, $x^2+2x-3$, $X^2+3x-4$
(iv) $18(x^3-9x^2+8x)$, $24(x^2-3x+2)$
(v) $36(3x^4+5x^3-2x^2)$, $54(27x^4-x)$

Solution:

(i)

\begin{align} x^2+5x+6&=x^2+3x+2x+6,\\ &=x(x+3)+2(x+3)\\ &=(x+3)(x+2) \end{align}

\begin{align} x^2-4x-12&=x^2-6x+2x-12,\\ &=x(x-6)+2(x-6)\\ &=(x-6)(x+2) \end{align}

H.C.F= $x+2$

(ii)

\begin{align} x^3-27 &=x^3-3^3,\\ &=(x-3)(x^2+3x+9)\end{align}

\begin{align} x^2+6x-27&=x^2+9x-3x-27,\\ &=x(x+9)-3(x+9)\\ &=(x+6)(x-3) \end{align}

\begin{align} 2x^2-18&=2(x^2-9),\\ &=2(x^2-3^2)\\ &=2(x+3)(x-3) \end{align}

H.C.F= $x-3$

(iii)

\begin{align} x^3-2x^2+x &=x(x^2-2x+1),\\ &=x(x^2-x-x+1),\\ &=x(x(x-1)-1(x-1)),\\ &= x(x-1)(x-1)\end{align}

\begin{align} x^2+2x-3&=x^2+3x-x-3,\\ &=x(x+3)-1(x+3)\\ &=(x+3)(x-1) \end{align}

\begin{align} X^2+3x-4&=x^2+4x-x-4,\\ &=x(x+4)-1(x+4)\\ &=(x+4)(x-1) \end{align}

H.C.F= $x-1$

(iv)

\begin{align} 18(x^3-9x^2+8x) &=2 \times 3 \times 3x(x^2-9x+8),\\ &=2 \times 3 \times 3x(x^2-x-8x+8),\\ &=2 \times 3 \times 3x(x(x-1)-8(x-1)),\\ &= 2 \times 3 \times 3x(x-1)(x-8)\end{align}

\begin{align} 24(x^2-3x+2)&=2 \times 2 \times 2 \times 3(x^2-x-2x+2),\\ &=2 \times 2 \times 2 \times 3(x(x-1)-2(x-1)),\\ &=2 \times 2 \times 2 \times 3(x-1)(x-2)\end{align}

H.C.F= $6(x-1)$

(v)

\begin{align} 36(3x^4+5x^3-2x^2) &=4 \times 9 \times 2(3x^2+5x-2),\\ &=4 \times 9 \times 2(3x^2+6x-x-2),\\ &=4 \times 9 \times 2(3x(x+2)-1(x+2)),\\ &= 4 \times 9 \times 2(x+2)(3x-1)\end{align}

\begin{align} 54(27x^4-x)&=2 \times 3 \times 9x(27x^3-1),\\ &=2 \times 3 \times 9x((3x)^3-(1)^3),\\ &=2 \times 3 \times 9x(3x-1)(9x^2+3x+1)\end{align}

H.C.F= $18(3x-1)$

Find the L.C.M. of the following expressions by factorization.
(i) $39x^7y^3z$, $91x^5y^6z^7$
(ii)$102xy^2z$, $85x^2yz$ , $187xyz^2$

Solution:

(i)

\begin{align} 39x^7y^3z &=3 \times 13 x^7y^3z,\\ &=3 \times 13x^5x^2y^3z\end{align}
\begin{align} 91x^5y^6z^7 &=7 \times 13 x^5y^6z^7,\\ &=7 \times 13x^5y^2y^3zz^6\end{align}

\begin{align} L.C.M.&= (13x^5y^3z)(21x^2y^3z^6)\\ &=273 x^(5+2)y^(3+3)z^(1+6)\\ &=273 x^7y^6z^7 \end{align}

(ii)

\begin{align} 102xy^2z &=2 \times 3 \times 17 xyyz\end{align}
\begin{align} 85x^2yz &=5 \times 17 xxyz\end{align}
\begin{align} 187xyz^2 &=11 \times 17 xyzz\end{align}

\begin{align} L.C.M.&= (17xyz)(2 \times 5 \times 11xyz)\\ &=5610 x^2y^2z^2\end{align}

Find the L.C.M. of the following expressions by factorization.
(i) $x^2-25x+100$, $x^2-x-20$
(ii) $x^2+4x+4$, $x^2-4$,$2x^2+x-6$
(iii) $2(x^4-y^4)$,$3(x^3+2x^2-xy^2-2y^3)$
(iv) $4(x^4-1)$, $6(x^3-x^2-x+1)$

Solution:

(i)

\begin{align} x^2-25x+100 &=(x^2-5x-20x+100)\\ &=(x(x-5)-20(x-5))\\ &= (x-5)(x-20)\end{align}

\begin{align} x^2-x-20&=x^2-5x+4x-20\\ &=x(x-5)+4(x-5)\\ &=(x-5)(x+4) \end{align}

L.C.M.= $(x-5)(x-20)(x+4)$

(ii)

\begin{align} x^2+4x+4 &=(x^2+2x+2x+4)\\ &=(x(x+2)+2(x+2))\\ &= (x+2)(x+2)\end{align}

\begin{align} x^2-4 &=(x-2)(x+2) \end{align}

\begin{align} 2x^2+x-6 &=(2x^2+4x-3x-6)\\ &=(2x(x+2)-3(x+2))\\ &= (x+2)(2x-3)\end{align}

L.C.M.= $(x+2)^2(x-2)(2x-3)$

(iii)

\begin{align} 2(x^4-y^4)&=2((x^2)^2-(y^2)^2)\\ &=2((x^2-y^2)(x^2+y^2))\\ &= 2(x-y)(x+y)(x^2+y^2)\end{align}

\begin{align} 3(x^3+2x^2-xy^2-2y^3)&=3(x^2(x+2y)-y^2(x+2y))\\ &=3(x+2y)(x^2-y^2)\\ &=3(x+2y)(x-y)(x+y) \end{align}

\begin{align} L.C.M.&= 2 \times 3 (x+y)(x-y)(x+2y)(x^2+y^2)\\ &=6 (x^4-y^4)(x+2y)\end{align}

(iv)

\begin{align} 4(x^4-1)&=2 \times 2((x^2)^2-(1^2)^2)\\ &=2 \times 2((x^2-1)(x^2+1))\\ &= 2 \times 2(x-1)(x+1)(x^2+1)\end{align}

\begin{align} 6(x^3-x^2-x+1)&=2 \times 3(x^2(x-1)-1(x-1))\\ &=2 \times 3(x-1)(x^2-1)\\ &=2 \times 3(x-1)^2(x+1) \end{align}

\begin{align} L.C.M.&= 2 \times 2 \times 3 (x+1)(x-1)(x-1)(x^2+1)\\ &=12 (x^4-1)(x-1)\end{align}

For what value of $k$ is $(x+4)$ the H.C.F. of $x^2+x-(2k+2)$ and $2x^2+kx-12$ ?

Solution:

$(x+4)$ will divide completely $x^2+x-(2k+2)$ and $2x^2+kx-12$.

\begin{align} p(x)&=x^2+x-2k-2 \end{align}

put $x=-4$

\begin{align} p(-4)&=(-4)^2+(-4)-2k-2 \\&= 16-4-2k-2\\&=10-2k\\&=R \end{align}

$R$ must be zero.

therefore \begin{align}10-2k &=0 \end{align}

\begin{align}-2k &=-10\end{align}

\begin{align}k &=5\end{align}

\begin{align} q(x) &=2x^2+kx-12 \end{align}

put \begin{align} x &=5 \end{align}

\begin{align} q(-4) &=2(-4)^2-4k-12 \\&=32-4k-12\\&=20-4k\\&=R\end{align}

$R$ must be zero.

\begin{align} 20 -4k &= 0 \end{align}

\begin{align} -4k &= -20 \end{align}

\begin{align} k &= 5 \end{align}

If $(x+3)(x-2)$ is the H.C.F. of $p(x)=(x+3)(2x^2-3x+k)$ and $q(x)=(x-2)(3x^2+7x-l)$, Find $k$ and $l$.

Solution:

$(x+3)(x-2)$ will divide completely $p(x)$ and $q(x)$.

\begin{align} p(x)&=(x+3)(2x^2-3x+k) \end{align}

put $x=2$

\begin{align} p(2)&= (2+3)(2(2)^2-3(2)+k)\\&= 5(8-6+k)\\&=5(2+k)\\&=R \end{align}

$R$ must be zero.

therefore \begin{align}5(2+k) &=0 \end{align}

\begin{align}2+k &=0\end{align}

\begin{align}k &=-2\end{align}

\begin{align} q(x) &=(x-2)(3x^2+7x-l) \end{align}

$(x+3)(x-2)$ will divide completely $q(x)$.

put \begin{align} x &=-3 \end{align}

\begin{align} q(-3) &=(-3-2)(3(-3)^2+7(-3)-l) \\&=(-5)(27-21-2l)\\&=(-5)(6-l)\\&=R\end{align}

$R$ must be zero.

\begin{align} (-5)(6-l) &= 0 \end{align}

\begin{align} 6-l &= 0 \end{align}

\begin{align} l &= 6 \end{align}

The L.C.M. and H.C.F. of two polynomials $p(x)$ and $2(x^4-1)$ and $(x+1)(x^2+1)$ respectively. If $p(x)= x^3+x^2+x+1$, find $q(x)$ are

Solution:

We know $P(x) \times q(x)= L.C.M \times H.C.F.$

\begin{align} x^3+x^2+x+1 \times q(x)&=2(x^4-1)(x+1)(x^2+1)\end{align}

\begin{align} q(x)&=\frac{2(x^4-1)(x+1)(x^2+1)}{x^3+x^2+x+1}\\&=\frac{2(x^4-1)(x+1)(x^2+1)}{x^2(x+1)+1(x+1)}\\&=\frac{2(x^4-1)(x+1)(x^2+1)}{(x+1)(x^2+1)}\\&=2(x^4-1) \end{align}

Let $p(x)= 10(x^2-9)(x^2-3x+2)$ and $q(x)= 10x(x+3)(x-1)^2$. If the H.C.F. of $p(x)$ , $q(x)$ is $10(x+3)(x-1)$, find their L.C.M.

Solution:

We know $P(x) \times q(x)= L.C.M \times H.C.F.$

\begin{align} 10(x+3)(x-1) \times q(x)&=10(x^2-9)(x^2-3x+2)10x(x+3)(x-1)^2\end{align}

\begin{align} q(x)&=\frac{10(x^2-9)(x^2-3x+2)10x(x+3)(x-1)^2}{10(x+3)(x-1)}\\&=(x^2-9)(x^2-3x+2)10x(x-1)\\&=10x(x^2-9)(x-1)(x^2-3x+2)\\&=10x(x^2-9)(x-1)(x^2-2x-x+2)\\&=10x(x^2-9)(x-1)(x(x-2)-1(x-2))\\&=10x(x^2-9)(x-1)(x-2)(x-1)\\&=10x(x^2-9)(x-1)^2(x-2)\end{align}

Let the product of L.C.M. and H.C.F. of two polynomials be $(x+3)^2(x-2)(x+5)$. If one polynomial is $(x+3)(x-2)$ and the second polynomial is $x^2+kx+15$, find the value of k.

Solution:

We know L.C.M. \times H.C.F = (x+3)^2(x-2)(x+5)

\begin{align} p(x)&=(x+3)(x-2)\end{align}

\begin{align} q(x)&=x^2+kx+15 \end{align}

$P(x) \times q(x)= L.C.M \times H.C.F.$

\begin{align} (x^2+kx+15)(x+3)(x-2)&= (x+3)^2(x-2)(x+5)\end{align}

\begin{align} (x^2+kx+15)&= \frac{(x+3)^2(x-2)(x+5)}{(x+3)(x-2)}\end{align}

\begin{align} (x^2+kx+15)&= (x+3)(x+5)\end{align}

\begin{align} x^2+kx+15&= x^2+8x+15\end{align}

\begin{align} kx&= x^2+8x+15-x^2-15\end{align}

\begin{align} kx&= 8x\end{align}

\begin{align} k&= 8\end{align}

• matric/9th_science/ex-6-1